Analisis Manajemen Risiko Pembiayaan Kpr Griya Dengan Akad Murabahah Pada Bank Syariah Indonesia Kc Medan Gajah Mada - Cut Ernita Julistia; Isra Hayati (CERED Indonesia Institute, 2022)
This study aims to determine the risks that occur in financing Griya Home Ownership Loans for murabaha contracts, find out the application of risk management and find out the obstacles that occur at Bank Syariah Indonesia KC Medan Gajah Mada. The research approach used is a qualitative research method with a descriptive approach. The Data Collection Techniques used in this study are observation, interviews, documentation, and literature studies. The data validity technique uses the triangulation method. Respondents in this study consisted of Consumer Banking Relationship Manager and Admin Micro Powning Staff. The results showed that the risks that occurred at Bank Syariah Indonesia KC Medan Gajah Mada in financing home ownership loans under the Murabaha contract were financing or credit risks, operational risks, and market risks caused by bad debts, the existence of defaults and changes in market variables but rarely occur. The implementation of risk management is carried out by following the guidelines of Bank Indonesia regulation No.11/25/PBI/2009, Article 4 Paragraph 3 for Islamic Commercial Banks is required to apply four types of risk, namely Credit or financing risk, market risk, liquidity risk, and operational risk.